The Concept of Qiwāmah in the Perspective of Feminist Activists Amina Wadud and Zainab al-Ghazali - Aqidatul Islamiyah; A. Faizul Mubin; Zubeir Mohamad Nur Sholeh (Yayasan Pesantren Mahasiswa An-Nur, 2024)
The debate on the leadership roles of men and women (qiwāmah) in Islam is often associated with different interpretations of religious texts. This article aims to uncover and compare the concept of